PENYUSUNAN MONITORING DAN EVALUASI RENCANA INDUK KELITBANGAN TAHUN 2022: PENYUSUNAN MONITORING DAN EVALUASI RENCANA INDUK KELITBANGAN TAHUN 2022 - Fadillah Amin; Lintang Edityastono; Eko budi Valianto (Bappeda Kota Malang, 2023)
Abstract: In accordance with the Regulation of the Minister of Home Affairs of the Republic of Indonesia Number 17 of 2016 concerning Guidelines for Research and Development at the Ministry of Home Affairs and Regional Government, in order to carry out the research and development function, it is necessary to develop a policy framework for research and development for the domestic government and regional governments that accommodate various aspects of governance in a comprehensive and synergistic concept of a research plan. The Department of Public Works, Spatial Planning, Housing and Residential Areas has the largest percentage, namely 10%, while the Environmental Laboratory Technical Implementation Unit has the smallest percentage, namely 1%. The percentage of implementation of R&D Programs/Activities Plans has increased in 2019 by 71.07% to 80.86% in 2020, then 94.81% in 2021 then in 2022 to 99.30% and increased again by 100% in year 2023.